Multistatic hybrid SAR/ISAR data generation using a stationary target - Rattan, Anmol; Andre, Daniel; Finnis, Mark V. (Institution of Engineering and Technology (IET), 2022)
There is great interest in multistatic synthetic aperture radar (SAR) systems as they are capable of providing high resolution images. These systems could prove promising candidates for provision of surveillance for both military and civilian interest. Both multistatic SAR and its counterpart, multistatic inverse synthetic aperture radar (ISAR), are limited by their assumptions of observing a stationary target from a moving platform and vice-versa. Hence, without adequate target motion compensation, their resultant radar images appear defocused. Arranging experiments capable of providing repeatable multistatic hybrid SAR/ISAR data of real moving targets can be difficult and costly. One viable approach is the novel method presented in this study, whereby multistatic hybrid SAR/ISAR data can be collected of a target moving with a theoretical motion, without the requirement of an actual moving target – the theoretical motion is brought about through the appropriate motion of antennas. The study demonstrates, both through simulation and experimentation, how radar trajectories of a given SAR system can be altered to arrive at the equivalent setup of observing a moving target. Results from simulation and from an experiment conducted at the Cranfield University Ground-Based SAR (GBSAR) laboratory are presented, showing the utility of this approach.
Keywords: multistatic; hybrid SAR/ISAR; six-degrees-of-freedom motion; motion estimation